LOBSTER FISHERY OFF THE SOUTH-WEST COAST OF INDIA Anchor Hook and Trap Fisheries - Miyamoto, H; Shariff, A T (Indian Journal of Fisheries, 2011)
LOBSTERS as excellent food of delicacy are widely acclaimed and have a worldwidemarket. South Africa, Australia and Cuba rank best in the spiny lobsterfisheries as can be seen by their exports to U.S.A., during 1956